HUBUNGAN ARAB SAUDI DAN MESIR PADA MASA PEMERINTAHAN ABDEL FATTAH AL-SISI DALAM KONFLIK SURIAH - Surez, Muhammad Farhan; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to examine the relationship between two mutually influential countries in the Middle East region, namely Saudi Arabia and Egypt. Relations between the two countries have experienced various dynamics, either as rivals or allies. Relations between Saudi Arabia and Egypt, which had deteriorated after the fall of the Hosni Mubarak regime caused by the Arab Spring, recovered after the rise of Abdel Fattah Al-Sisi to the reins of Egyptian power after the coup of Muhammad Morsi's government, which incidentally is a figure affiliated with the Muslim Brotherhood (MB).  Saudi Arabia played an important role in the coup carried out by Al-Sisi, but the relations between the two countries became heated again after the differences in interests in the Syrian conflict.The results of this study indicate that the Syrian conflict has created new dynamics for the relationship between Saudi Arabia and Egypt. The occurrence of differences in interests in responding to the Syrian conflict has caused heated relations between Saudi Arabia and Egypt as evidenced by the negative response given by Saudi Arabia to Egypt's support for the Bashar Al-Assad regime in Syria. Saudi Arabia wants the fall of the Assad regime in Syria due to rival interests for regional dominance with Iran as well as Sunni and Shia ideological rivalries with Iran. While on the other hand, Egypt wants the Assad regime in Syria to remain stable so that Al-Sisi's power in Egypt is not threatened by the influence of Islamist and extremist groups such as MB.Keywords: Saudi Arabia and Egypt Relation, Middle East, Syrian Conflict, Regional Domination, Sunni, Shia